1998
DOI: 10.1046/j.1365-2362.1998.00305.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromogranin A: its clinical value as marker of neuroendocrine tumours

Abstract: Chromogranin A (CgA) belongs to a family of secretory proteins that are present in densecore vesicles of neuroendocrine cells. Owing to its widespread distribution in neuroendocrine tissues, it can be used as an excellent immunohistochemical marker of neoplasms of neuroendocrine origin. It can also serve as serum marker of neuroendocrine activity because it is co-released with the peptide hormone content of the secretory granules. The serum concentration of CgA is elevated in patients with various neuroendocri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
73
1
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(87 citation statements)
references
References 92 publications
9
73
1
4
Order By: Relevance
“…Patients with renal failure or severe hepatic dysfunction were excluded from the study to avoid spuriously elevated CgA levels (3,8).…”
Section: Sporadic Gep Netsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with renal failure or severe hepatic dysfunction were excluded from the study to avoid spuriously elevated CgA levels (3,8).…”
Section: Sporadic Gep Netsmentioning
confidence: 99%
“…CgA immunohistochemical detection is a main step in the diagnosis of neuroendocrine tumors (NETs) (3). Also, circulating CgA levels have been claimed to be a useful marker for these tumors, with a high specificity and a sensitivity ranging from 27 to 81% depending on their origin (2 -8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For tumour diagnosis, however, it is advantageous to measure the intact molecule and thereafter if desired to measure whichever fragments that may give additional information as these may vary greatly between each tumour. 82 For diagnostic purposes, the measurement of intact CgA is the best chemical screening tool for NETs.…”
Section: Chromogranin Bmentioning
confidence: 99%
“…Concentrations may be dependent on tumor features, such as: type, secretory activity, neuroendocrine differentiation degree and total burden (1,2). However, several lines of evidence show that the diagnostic accuracy is affected primarily by the type of assay used to measure CgA (1,(3)(4)(5). As a matter of fact, it has been reported that in healthy subjects, there is a discordance rate of ;20% between CgA concentrations measured using the two commercially available methods: immunoradiometric assay (IRMA) and enzyme-linked immunosorbent assay (ELISA) (1).…”
Section: Introductionmentioning
confidence: 99%